THE USE OF TOP-DOWN AND BOTTOM-UP LISTENING STRATEGIES TO IMPROVE MOROCCAN UNIVERSITY STUDENTS’ LISTENING COMPREHENSION AND LANGUAGE SKILLS - Benjelloun, Mounia (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Listening is one of the most challenging skills for language learners; although they spend time listening to the teacher, their fellow students, and recordings, they are rarely exposed to listening strategies, which can help them become more effective and efficient listeners. Teaching methods mainly focus on productive skills compared to the listening skill, which has been considered the least understood and the most overlooked, until recently. (Nation & Newton, 2009). As a result, students encounter listening comprehension challenges and lack the appropriate language skills needed to complete listening and speaking tasks successfully. This study is, therefore, an attempt to investigate the impact of top-down and bottom-up listening strategies on improving Moroccan university students’ listening comprehension and language skills. Two groups of students, a controlled and an experimental, belonging to the same year and field took part in this study. Both groups were exposed to a pre-listening and a post-listening test, followed by speaking tasks. They were also exposed to listening tasks for about twelve weeks. The experimental group, however, were explicitly taught listening strategies for all stages of the listening tasks. This study adopts a qualitative approach to compare and analyze the results. Preliminary findings reveal that generally, both the controlled and experimental group improved their listening skills for gist. However, the use of bottom-up listening strategies has significantly proved effective in helping students of the experimental group to develop their listening comprehension for specific information and their oral production, which was more meaningful and efficient than that of the controlled group.